Women in Spanish film and TV movies (2000-2012): representations, subjects and contexts - Gámez Fuentes, María José (Historia y Comunicación Social, 2014)
This paper aims at analysing the representation and participation of women in Spanish films and TV movies according to the following parameters: how do audiences validate inherited gender roles through box office results, how do films relate women’s experiences during democracy with social imaginaries constructed upon long shared narratives, how does the industry articulate women’s contribution.
Keywords: women; gender; Spanish cinema; TV movies; representation; audiences.